Current techniques in rice mill effluent treatment: Emerging opportunities for waste reuse and waste-to-energy conversion. (December 2016) - Kumar, Anuj; Priyadarshinee, Rashmi; Roy, Abhishek; Dasgupta, Dalia; Mandal, Tamal
Abstract: Rice mills release huge volumes of wastewater and other by-products when processing paddy rice. The wastewater often contains toxic inorganic and organic contaminants which cause environmental damage when released. Accordingly, cost-effective techniques for removing contaminants are needed. This article reviews current processes for curbing pollution and also reusing and recycling waste products. Novel techniques exist for converting waste products into energy and value-added products. Graphical abstract: Highlights: Possible solutions for the minimization of waste and harvesting of resources. Emergence of techniques for the generation of energy and value-added products. Co-existence of rice mill wastewater treatment along with solid waste management.